PERENCANAAN ULANG STRUKTUR GEDUNG PRASETIYA MULYA BUSINESS SCHOOL - Jihan Zahara Winanti; Hanik Kurniyati R.; Windu Partono; Hardi Wibowo (Jurnal Karya Teknik Sipil, 2014)
Design of the building structure was done in order to standing and strong receiving a load on it. Each one of the building structure with another building structure certainly have differences,  the differences include the strength of materials, use of materials, dimensions of the cross section, the calculation of the structure, work stage and so on. This difference is causes the strength of each structure is different, and also differences in cost of structure.Therefore, we would like to know differences of  strength and costs resulting from redesign of the Prasetiya Business School building by eliminating shearwall and open-frame method. Redesign on this structure using the method System Bearer Special Moment.